NDSP 06: Prevalence and risk factors for obesity in urban and rural areas of Pakistan: A study from second National Diabetes Survey of Pakistan (NDSP), 2016–2017. Issue 1 (January 2021) - Basit, Abdul; Askari, Saima; Zafar, Jamal; Riaz, Musarrat; Fawwad, Asher; ,
Abstract: Objective: To study the pattern and prevalence of obesity in a large representative sample of Pakistani population aged 20 years and above. Methodology: This study is a sub analysis of the second National Diabetes Survey of Pakistan (NDSP) 2016–2017, a large community-based epidemiological survey carried out from February 2016 to August 2017 in all 4 provinces of Pakistan. An estimated sample size of 10, 834 people was calculated using a multistage sampling technique. Out of 213 clusters, Twenty-seven clusters were selected from all four provinces of Pakistan. Households were identified and selected members of every 10th household were advised to come to the campsite after an overnight fast. All the study participants underwent anthropometric measurements including height, weight, and waist circumference by using standardized techniques and oral glucose tolerance tests were done. Data were analyzed on the statistical package for social sciences (SPSS), version 20. Results: Overall weighted prevalence of generalized obesity was 57.9% (42% in males and 58% in females) and central obesity 73.1% (37.3% in males and 62.7% in females) as per WHO Asia pacific cutoffs. The highest prevalence of generalized obesity was found in Punjab 60%, followed by Khyber, Pakhtunkhwa 59.2%. Moreever, highest prevalence of abdominal obesity was observed in Baluchistan 82.1%, followed by Punjab 73.3%. Obesity (generalized and abdominal) was found significantly associated with diabetes, hypertension, and dyslipidemia. Conclusion: The prevalence of obesity is at epidemic proportions in Pakistan, calling for urgent lifestyle intervention strategies to prevent and manage this important cardiometabolic risk factor.